Dual-Process Model of Consumer Responses to Deceptive Patterns in E-Commerce - Dang, Duong; Havinen, Laura; Pasanen, Tomi A.; Mäkipää, Juho-Pekka (Association for Information Systems, 2026)
Deceptive patterns are increasingly prevalent in e commerce interfaces, exploiting users’ cognitive vulnerabilities to nudge them toward unintended actions such as subscriptions or premium upgrades. Although prior research has examined these patterns and their negative effects, it has given limited attention to the cognitive mechanisms that determine whether users succumb to manipulation or regain autonomy. This study presents the Dual Process Deceptive Pattern Response Model, which explains transitions from intuitive exploitation to reflective recovery. Drawing on qualitative approach with abductive analysis, we show that deceptive patterns primarily hijack System 1 (fast, intuitive processing), while expectation violations activate System 2 (deliberate reasoning). This transition enables reasoned recognition, protective intentions, and a reinforcing feedback loop that strengthens long term resistance. The model advances deception detection scholarship by shifting the focus from content based falsehoods to interface embedded deception. Practically, it provides levers to reduce System 1 exploitation and accelerate System 2 recovery, preserving user autonomy in e commerce.
Keywords: Deceptive patterns; dark patterns; deceptive design; qualitative approach; abductive thematic analysis; dual-process theory; e-commerce; fi=Tietojärjestelmätiede|en=Information Systems Science|; fi=Tietotekniikka tekn|en=Information Technology tech|